Spectroscopic characterization and biological activity of salicylaldehyde thiazolyl hydrazone ligands and their metal complexes - Cukurovali, A; Yilmaz, I; Kirbag, S (Springer, 2006)
Two novel bidentate Schiff base ligands, 2-(2-hydroxy-3,5-dichloro/diboromo) benzaldehyde-[4-(3-methyl-3-mesitylcyclobutyl)-1,3-thiazol-2-yl]hydrazone, (LH)-H-1, (LH)-H-2 and their transition metal complexes are reported. The new ligands and their complexes have been characterized by elemental analyses, Lambda(M), infrared, u.v.-vis, H-1- and C-13-n.m.r. spectroscopy, and magnetic susceptibility measurements. The thermal properties of all complexes have been investigated by TG technique. The complexes contain two monoanionic, bidentate NO ligands. It was found that all the complexes are mononuclear. Antimicrobial activities of the ligands and their complexes have been tested against five different microorganisms, and some of the complexes were found to be active against some of the microorganisms studied.
Keywords: Antiinflammatory Activity; Derivatives; Agonist; Co(Ii); Cancer; Potent; Ni(Ii); Acids